PRESEPSI GURU TENTANG PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SMA NEGERI SE-KOTA PARIAMAN - Nurul Asnah; Jasrial (Global Action and Education for Society, 2023)
The background of this research is the problems found in the use of BOS funds in State Senior High Schools in Pariaman City. This study aims to gather information about teachers' perceptions about the use of BOS School Operational Assistance Funds in public high schools in Kota Pariaman in terms of 1) utilization for the acceptance of new students 2) utilization for library development, 3) utilization for carrying out assessment activities and evaluation of learning, 4) utilization for the professional development of teachers and education staff, 5) utilization for maintenance of school facilities and infrastructure, 6) utilization for financing school management, 7) utilization for procuring consumable learning practicum equipment. This type of research is descriptive. The population of the study was teachers at Public High Schools in Kota Pariaman, totaling 263 people. The sample in this study were 73 people. The sampling was carried out using the Proportional Stratified Random Sampling technique. The instrument in this study was a Likert scale model questionnaire with answer choices, namely Very Good (SB), Good (B), Fairly Good (CK), Not Good (KB), Not Good (TB). This research questionnaire has been tested for validation and reliability, then the data is processed using the average formula (mean). The results of the study indicated that teachers' perceptions of the use of School Operational Assistance funds in Public High Schools throughout Kota Pariaman in aspects 1) Utilization of BOS funds for new student admissions with an average score of 4.11 were in the good category, 2) utilization for library development with an average score of 4.22 was in the good category, 3) utilization for carrying out learning assessment and evaluation activities with an average score of 4.16 was in the good category, 4) utilization for the professional development of teachers and education staff with an average score of 3, 94 is in the good category, 5) utilization for maintenance of school facilities and infrastructure with an average score of 4.07 is in the good category, 6) utilization for financing school management with an average score of 4.03 is in the good category, 7) utilization for the procurement of consumables for learning practice with an average score of 3.94 is in the good category. Thus it can be concluded that the use of BOS funds in Public High Schools throughout Pariaman City is in the good category with an average score of 4.06.